Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1016/s0928-8244(99)00123-6
|View full text |Cite
|
Sign up to set email alerts
|

Grouping of 20 reference strains of Legionella species by the growth ability within mouse and guinea pig macrophages

Abstract: 20 Reference strains of Legionella species, isolated from human, were classified according to their ability to grow within thioglycolate-induced peritoneal macrophages of mice and guinea pigs. Inbred and congenic mice were used to study the effect of the natural resistance genes Lgn1 and Bcg that are expressed phenotypically in the mouse macrophages. The Lgn1 gene controlled the intracellular growth of Legionella pneumophila Philadelphia-1 and Legionella jordanis GIFU 12657, but the Bcg gene did not affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…There is no direct correlation with the grouping in this study, which could be due to the differences in the strains and/or methods of classification. This is not surprising as Izu et al (1999) found no significant characteristics common to another grouping done by Neumeister et al (1997), which was based on the bacterial doubling time in Mono Mac 6 cells and Acanthamoeba castellanii. Our data on L. cincinnatiensis are consistent with the finding of Izu et al (1999) that this species of Legionella does not grow within U937 cells despite the fact there might be some strain differences and different host cell lines used.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…There is no direct correlation with the grouping in this study, which could be due to the differences in the strains and/or methods of classification. This is not surprising as Izu et al (1999) found no significant characteristics common to another grouping done by Neumeister et al (1997), which was based on the bacterial doubling time in Mono Mac 6 cells and Acanthamoeba castellanii. Our data on L. cincinnatiensis are consistent with the finding of Izu et al (1999) that this species of Legionella does not grow within U937 cells despite the fact there might be some strain differences and different host cell lines used.…”
Section: Discussionmentioning
confidence: 54%
“…This is not surprising as Izu et al (1999) found no significant characteristics common to another grouping done by Neumeister et al (1997), which was based on the bacterial doubling time in Mono Mac 6 cells and Acanthamoeba castellanii. Our data on L. cincinnatiensis are consistent with the finding of Izu et al (1999) that this species of Legionella does not grow within U937 cells despite the fact there might be some strain differences and different host cell lines used. However, the main objective of this study was not to provide a classification method for Legionella spp., but rather to provide a better understanding of the pathogenic trait(s) that could be responsible for variation in the virulence of these bacteria.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations